The Impact of Respite Programming on Caregiver Resilience in Dementia Care: A Qualitative Examination of Family Caregiver Perspectives - Emily Roberts PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing, 2018)
Family members with a relative with dementia often experience what has been called the “unexpected career of caregiver” and face multifaceted, complex, and stressful life situations that can have important consequences. This exploratory study was designed to address this major public health challenge through the lens of caregiver resilience and caregiver respite programming. While many caregivers report that they derive significant emotional and spiritual rewards from their caregiving role, many also experience physical and emotional problems directly related to the stress and demands of daily care. One way to alleviate these demands is the growing respite care field, providing services in a variety of settings for caregiver. Through qualitative analysis from face-to-face interviews with 33 family caregivers of individuals with dementia, several themes emerged describing the path to caregiver resilience which include family dynamics, isolation, financial struggles, seeking respite, and acceptance. While much research focuses on a caregiving burden perspective, the innovation of the present study is applying the resilience framework to outcomes from respite programming.